Florida 4-H Horse Member Advancement Program Level 2 - Edward L. Johnson; R. L. Horton (EDIS)
This document is 4HSWG04 of the Florida 4-H Youth Development Program, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Printed Janunary1989. Reviewed June 2002.